ENTERPRISE RISK MANAGEMENT AND FIRM VALUE: EVIDENCE FROM STATE-OWNED ENTERPRISE IN INDONESIA - Hudi Kurniawanto; Rispantyo; Krisna Puji Rahayu (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
This study aims to provide empirical evidence of the influence of enterprise risk management on firm value. This study also uses leverage and profitability as control variables. The research population is State-Owned Enterprises listed on the Indonesia Stock Exchange in 2020-2021. The sampling method used is the purposive sampling method, the number of samples according to the criteria of 40 annual reports. The data analysis tool used in this research is multiple linear regression analysis. The results of this study prove that enterprise risk management has a significant positive effect on firm value while leverage and profitability do not affect firm value.Keywords: Enterprise Risk Management, Leverage, Profitability, Firm Value, Indonesia Stock Exchange